Long‐term stability of invisible X‐ray fluorescence identification tags. (11th November 2019) - Benetková, Barbora; Krejčí, Jan; Drábková, Klára; Ďurovič, Michal; Veselý, Michal; Dzik, Petr; Akrman, Jiří
Abstract: The traditional labelling of archive documents (e.g., hand stamping) entails several limitations. It could affect the aesthetic value of the archive document and is easy to find and remove in case of the theft of the document. The use of a label that would not be easily visible by the naked eye would resolve both of these problems. One possibility in designing such label is the use of the elements that have a good response in X‐ray fluorescence (XRF) spectrum, are not disturbing in colour, and are not usually present in the archive materials themselves. This study focuses on such type of labelling, specifically, the tags based on the oxides of lanthanum, dysprosium, samarium, gadolinium, and niobium. For the material to be taken into account by the community, it has to fulfil several important characteristics, such as harmlessness to the archival documents, non‐toxicity, or long‐term stability. In the study, the long‐term stability of these tags was studied on model samples of lignocellulose materials subjected to several types of artificial ageing. The colour changes and changes in the intensity of the responses of the individual elements in the XRF spectra were evaluated. To simulate the practical use, the tags of minimal visibility to the naked eye were printed on samples of real archive materials, and their potential for detection using a handheld XRF spectrometer was studied. Both of the research parts should help bring this type of labelling closer to the field application.